Developing the 'Polite Palsa' E-Comic: Integrating Extemporaneous Methods to Enhance Polite Speaking Skills in Primary Education - Hasanah, Radita; Purwati, Panca Dewi (Universitas Pendidikan Mandalika, 2025)
This research is motivated by the low value of polite speaking skills. This is due to the use of suboptimal learning methods, the use of suboptimal learning models, inadequate learning media, and inadequate school infrastructure. This study aims to determine the feasibility and effectiveness of E-Comic Polite Pals media for grade I elementary school students. This type of research is a development research with the Borg and Gall Research and Development model. Data collection used observation, interview, documentation, questionnaire, and oral test techniques. The data analysis techniques used were the normality test, t-test, Wilcoxon test, and N-Gain test. The results of the E-Comic Polite Pals media feasibility assessment from media experts obtained a score of 95%. The assessment from the material expert obtained a score of 91.25%. The assessment from the material expert obtained a score of 91.25%. The effectiveness of Polite Pals E-Comic media on polite speaking skills material was proven in the t-test and Wilcoxon test, with small-scale trial results involving 6 elementary school grade I students with high, medium, and low levels of speaking skills, obtained a significance value (2-tailed) of 0.000 < 0.05. In a large-scale trial involving 28 elementary school grade students, some of whom experienced difficulties in speaking skills, a significance value (2-tailed) of 0.000 < 0.05 was obtained. The average increase in Pretest to Posttest of large group product trials was 21.11 (60.35 increased to 81.46). The results of the small-scale N-Gain test obtained an N-Gain of 0.46, and in the large-scale product trial, an N-Gain of 0.53. Based on data analysis, the Polite Pals E-Comic media is feasible and effective in learning the polite speaking skills of lower-class students.